HUBUNGAN PENGGUNAAN KONTRASEPSI HORMONAL DENGAN KEJADIAN STROKE - Yusmahenry Galindra; Erika Kusumawardani; Aulia Cesarany (Universitas Batam, 2025)
ABSTRACT Background: Stroke is a condition characterized by local and global neurological disorders that can progress, continue for more than 24 hours, and result in death. One of the risk factors for stroke is the use of contraception. Hormonal contraceptives containing estrogen and progesterone can significantly change the coagulation system by increasing the activity of thrombin and clotting factors and reducing the action of natural anticoagulants. Methods: : This type of research uses the Case Control method with an analytical observational approach. The study population was all stroke sufferers recorded in the medical records at RSBK in 2023, totaling 155 patients. This study used a sample of 80 patients. Where 40 patients were controls and 40 patients were cases. Results: The results of the Chi-Square analysis test show that the use of hormonal contraceptives is not related to the incidence of stroke at Budi Kemuliaan Hospital, Batam City in 2023 with a value of p=0.70 (>0.05). Conclusion: Based on the research results, it was found that there was no significant relationship between the use of hormonal contraception and the incidence of stroke at Budi Kemuliaan Hospital, Batam City in 2023. Keywords: Hormonal Contraception, Stroke, Used